Shifts in morphology and diet of non-native sticklebacks introduced into Japanese crater lakes - Adachi, Tatsuya (Blackwell Publishing Ltd, 2012)
An increasing number of exotic animals are causing ecological problems. Therefore, for better ecosystem management, it is important to understand how exotic species colonize and adapt to novel environments. The threespine sticklebacks (Gasterosteus aculeatus) can be a good vertebrate model system to explore the ecological and genetic mechanisms of adaptation not only in natural populations, but also in non-native populations. Although morphological changes have been documented in several introduced populations of stickleback, little is known about the dietary changes during colonization into novel environments. Here, we investigated the morphological and dietary changes of exotic threespine stickleback populations introduced into three Japanese crater lakes (Lake Towada, Lake Kussharo, and Lake Shikotsu). Sticklebacks were introduced into the crater lakes likely along with salmonids transplanted for aquaculture. The stickleback population in Lake Kussharo had multiple mitochondrial haplotypes and had larger phenotypic variances than other crater lake stickleback populations that had only one mitochondrial haplotype. Compilation of historical data on the morphology and stomach contents of the Lake Towada stickleback population showed that substantial shifts in body size and stomach contents occurred after colonization. Some of these changes may be related to an outbreak of the Schistocephalus parasite. These results suggest that sticklebacks can change their morphology and trophic ecology when they colonize novel environments. Therefore, extreme care should be taken when salmonids are transported between watersheds for aquaculture and that long-term monitoring of exotic species is essential for ecosystem management. In addition, further genetic studies on phenotypic changes in crater lake sticklebacks would help elucidate the genetic mechanisms underlying the adaptation of exotic fishes to novel environments.